Selective Laser-Melted Alloy 625: Optimization of Stress-Relieving and Aging Treatments - Barbara Rivolta; Riccardo Gerosa; Davide Panzeri (Applied Sciences)
Additive manufacturing is an innovative solution to produce components characterized by complex geometries. The use of such parts requires a deep knowledge of their behavior under different service conditions, especially from mechanical and corrosion resistance points of view. One of the most well-known and employed materials produced by selective laser melting is nickel alloy 625. It is already commonly used in its conventional form, but the additive manufacturing technology, despite its higher production costs and lower productivity, is becoming competitive because of its excellent mechanical strength. It is in fact significantly higher compared to the conventionally manufactured alloy whose properties are often limited by the difficulty in retaining a fine grain size during plastic deformation and heat treatment. Even though the as-built performance is already quite good, further strength improvement can be attained upon tailored single- and double-aging treatments that are optimized starting from the experimental results obtained in the conventional alloy and also considering the influence on corrosion resistance. In addition, considering that the stress-relieving treatment recommended for the conventional forged alloy at 870 °C is not suitable for the selective laser-melted material because of the more rapid precipitation response, this temperature is optimized to improve both the tensile deformability and the corrosion behavior.